Operations management : an active learning approach - Bicheno, John. (Blackwell, 1997)
Introduction to operations management. Product planning and positioning. Process design. Managing demand and supply of materials. Project management. Quality management. Productivity, methods and measurements. Scheduling and capacity. Time based operations.